(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The increasing digitalisation of education has significantly impacted music teacher training, integrating information and communication technologies (ICT) and online platforms into pedagogical practice. This study explores the role of digital ecosystems, particularly social media platforms like YouTube and TikTok, in shaping new approaches to music education. These platforms function not only as entertainment hubs but also as powerful educational tools that foster interactive learning, expand access to high-quality musical instruction, and engage students in dynamic ways. We analyse both the theoretical and practical aspects of ICT integration in music teacher education, highlighting how digital tools transform teaching methodologies. Special attention is given to social media as an educational resource, evaluating its benefits—such as accessibility, engagement, and diverse content—while also addressing challenges like quality control and information overload. Through expert analysis and case studies, we assess the effectiveness of blended learning models that combine traditional and digital education. As a result, we propose a structured model for integrating social media and online tools into music teacher training, aiming to enhance interactive engagement and professional development. This study contributes to the ongoing discussion on the modernisation of music education, offering practical recommendations for embedding ICT and social media into curricula. By leveraging the potential of digital learning environments, future music teachers can not only adapt to contemporary pedagogical challenges but also develop innovative teaching methodologies tailored to the needs of digital-native students.